Pancolonic endoscopic and histologic evaluation for relapse prediction in patients with ulcerative colitis in clinical remission. Issue 8 (1st March 2021) - Kaneshiro, Miyuki; Takenaka, Kento; Suzuki, Kohei; Fujii, Toshimitsu; Hibiya, Shuji; Kawamoto, Ami; Motobayashi, Maiko; Shimizu, Hiromichi; Nagahori, Masakazu; Saito, Eiko; Okamoto, Ryuichi; Ohtsuka, Kazuo; et al.
Summary: Background: Mucosal healing is an important treatment target in patients with ulcerative colitis. Aims: To explore the optimal colonoscopic strategy to determine the risk for clinical relapse in patients with ulcerative colitis. Methods: We enrolled 325 consecutive patients with ulcerative colitis in clinical and biochemical remission from April 2018 to March 2019. Five colonic segments were endoscopically and histologically assessed systematically. For endoscopic evaluation, we used three different modes of the Ulcerative Colitis Endoscopic Index of Severity (UCEIS): "original, " "worst affected, " and "pancolonic." The Geboes score was used for histological evaluation. We prospectively followed up the patients and defined clinical relapse as the primary endpoint. Results: Within 1 year after colonoscopy, 18.2% of patients experienced a clinical relapse. Receiver operating characteristic curve analysis showed areas under the curve of 0.755, 0.817, and 0.852 for the "original, " "worst affected, " and "pancolonic" groups, respectively; hence, pancolonic UCEIS obtained the highest predictive value. Using the pancolonic UCEIS cutoff value of 3, Kaplan–Meier curve analysis showed that patients with endoscopic activity had a significantly lower relapse‐free rate than those with endoscopic remission ( P  < 0.01). Multivariate analysis demonstrated endoscopic (pancolonic UCEIS >3) and histological (Geboes >3.0) activities as independent risks for relapse (HR: 3.96 and 3.48, respectively). Combining pancolonic UCEIS ≤3 and Geboes score ≤3.0 to provide 1‐year relapse avoidance was 92.0% sensitive and 97.0% specific. Conclusion: Evaluating disease remission by complete colonoscopy is relevant, and the combination of pancolonic endoscopic and histological evaluations may appropriately evaluate mucosal healing. Abstract : Combination of pancolonic endoscopic and histological evaluations predicts patients prognosis.